Zgodnja obravnava družin za razvoj varne navezanosti otrok z motnjo avtističnega spektra - Orel, Maša (Sodobna pedagogika, 2025)
A growing body of research suggests that early attachment in children with autism spectrum disorder (ASD) may be similar to that in children with normative development. However, authors find a lower proportion of secure attachment in children with ASD than in children with normative development. This may be due to a number of factors in the families of children with ASD that hinder the development of secure attachment between the child and parents. We conducted a systematic review of research focusing on early attachment in children with ASD. We included research for the last six years. We found that most authors focus on the specific characteristics of parents of children with ASD or families as factors of early attachment in children with ASD. By identifying and understanding the characteristics of individual families, effective early intervention support for families of children with ASD can be developed to improve the quality of life of the whole family. Research on early attachment in children with ASD has been carried out on relatively small samples, with different methodologies, with a variety of variables and sometimes mutually exclusive results. We make recommendations for further research in the field of early attachment and develop guidelines for early treatment of families of children with ASD that promote attachment.
Keywords: ASD; autism spectrum disorder; early intervention; MAS; motnja avtističnega spektra; parents; starši; zgodnja obravnava